Green Hydrothermal Synthesis of Ni(II)-MOF with Terephthalate-Pyrazine Mixed Ligands at Mild Condition - Finisia, Yenni; Tjahjanto, Rachmat Triandi; Prananto, Yuniar Ponco (The Journal of Pure and Applied Chemistry Research, 2024)
Ni(II) with mixed ligand of terephthalate-pyrazine (NiTP) metal complex can form metal-organic framework (MOF) material that offer many potential applications, such as adsorbent and/or photocatalyst for dye-based wastewater treatment. Production of the NiTP by hydrothermal method in a larger scale may economically unfavorable due to it requires high temperature and long reaction time. Green synthesis of NiTP by hydrothermal method using lower temperature and shorter reaction time was investigated in this study. The synthesis was done in Ni(II):T:P mol ratio of 1:1:4 at 150 áµ’C for 10 hours. The NiTP complex was characterized by infrared spectroscopy and powder-XRD. Crystallinity degree, thermal stability, band gap energy, and pore volume of the NiTP complex were compared to that of Ni(II)-terephthalate (NiT) complex, which was also made using the same condition, to study the effect of pyrazine addition on the properties of the NiTP. This study finds that the green microcrystalline NiTP complex was successfully obtained from mild reaction condition in good yield and identical to known MOF compound of [Ni(Î¼3-ter)(Î¼2-pyr)]n.(ter = terephthalate; pyr = pyrazine). Although the synthesized NiTP complex has lower crystallinity degree compared to the NiT complex, but it has better thermal stability, lower band gap energy, and bigger pore volume; therefore, it is possible to be further developed as adsorbent and/or photocatalyst for wastewater treatment.